2000
DOI: 10.1080/10789669.2000.10391253
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptive Fuzzy Algorithm for Domestic Hot Water Temperature Control of a Combi-Boiler

Abstract: This paper describes an innovative adaptive fuzzy control (AFC) algorithm for regulating the domestic hot water temperature of a combi-boiler or instantaneous hot water heater when using a domestic hot water flow rate sensor. The AFC automatically learns the feedforward relationship between the domestic hot water flow rate and the gas valve position and adapts to process changes such as variations in the inlet water temperature, controller set point, gas composition, and flow sensor miscalibration without requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Haissig and Woessner, [7], introduced an adaptation mechanism based on updating the location of the output membership function of a domestic hot water boiler FLC. Kolokotsa et al [8], describe the development of a model-following FLC based on scaling fuzzy inputs and outputs to respond to an idealised second-order model of a building space in order to achieve control over a variety of internal comfort conditions.…”
Section: Previous Workmentioning
confidence: 99%
“…Haissig and Woessner, [7], introduced an adaptation mechanism based on updating the location of the output membership function of a domestic hot water boiler FLC. Kolokotsa et al [8], describe the development of a model-following FLC based on scaling fuzzy inputs and outputs to respond to an idealised second-order model of a building space in order to achieve control over a variety of internal comfort conditions.…”
Section: Previous Workmentioning
confidence: 99%
“…The model was constructed for a car radiator and examined experimentally with the help of the water and air outlet temperature comparisons. Yang et al Haissig and Woessner [11] described an adaptive fuzzy control (AFC) algorithm for regulating the domestic hot water temperature of a combi boiler. The laboratory tests showed that an improvement in the set point error was achieved by reducing it between 18% and 70%.…”
Section: Introductionmentioning
confidence: 99%
“…When the flow occurs in the hot water installation, these devices automatically activate full heating power and heat the cold-water inlet to the required temperature parameters. Demand for heating power for such needs is usually higher than for space heating because water is heated in a continuous flow system [5][6][7]. According to Polish Regulations [8], provision of buildings with gas and installations should correspond to the needs and conditions resulting from the physicochemical properties of gas and the technical conditions for connection to the gas network, determined by the gas supplier.…”
Section: Introductionmentioning
confidence: 99%